Learning Organizations and Competitive Advantage as Mediating the Effect of Network Capability on Organizational Performance - Bunyamin Bunyamin; Kadarusman Kadarusman (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to test the effect between the Network Capability and Organizational Performance and Learning Organization, with the Competitive Advantage being served as the moderating variable conducted at Small and Medium Enterprises (SME) in Malang city. This study was done by distributing the questioners filled in by the owners and the heads of the small and medium enterprises firms in Malang city. The data was processed using smartpls program. The result shows that the Network Capability directly affects the Organizational Performance, Learning Organization, and Competitive Advantage. Organizational Performance is also directly and positively affected by the Learning Organization and Competitive Advantage. The indirect effect suggests that the Learning Organization and Competitive Advantage are variables that mediate the effect between the Network Capability and Organizational Performance and serve as partial mediation. Based on this study, it is hoped that it gives. This result is expected to give a deeper understanding of the importance of the strategy implementation referring to the resource-based view of the organization. The Network Capability improvement can be a trigger to develop the organization's learning capability, competitive and organizational performance. Practically, is expected to be implemented within an organization to collaborate either with internal or external parties